2020
DOI: 10.1002/wer.1344
|View full text |Cite
|
Sign up to set email alerts
|

Research on constructing sponge city indicator and decision evaluation model with fuzzy multiple criteria method

Abstract: Cities face acute shock like hurricanes and floods, and chronic stresses such as droughts, water shortages, urban floods, and urban using water. How cities can create a development model in which the water and environment can coexist to alleviate the problem with urban water has become a common problem faced by countries or cities. Sponge city construction becomes a possible option to meet these challenges. According to the dimensions of pre‐assessment, this article constructs the sponge city assessment indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 17 publications
(16 reference statements)
0
10
0
Order By: Relevance
“…There was further progress between 2003 and 2007, as megacities including Beijing began to better manage stormwater by improving their urban drainage systems and water pollution treatment works [47]. Between 2008 and 2010, water resource-optimization strategies were invoked to optimize the spatial redistribution of water resources [48]. In 2012, the city of Shenzhen began experimentally implementing LID [49].…”
Section: Urban Water Management Policies In Chinese Citiesmentioning
confidence: 99%
“…There was further progress between 2003 and 2007, as megacities including Beijing began to better manage stormwater by improving their urban drainage systems and water pollution treatment works [47]. Between 2008 and 2010, water resource-optimization strategies were invoked to optimize the spatial redistribution of water resources [48]. In 2012, the city of Shenzhen began experimentally implementing LID [49].…”
Section: Urban Water Management Policies In Chinese Citiesmentioning
confidence: 99%
“…In addition to the increase in disaster risk, land use changes will also bring a large amount of runoff increment. Flood flow increases with the increasing population density, which largely depends on the urban sprawl, the increase of impervious surfaces and the unresponsiveness of projects [16,17]. Studies have shown that land use changes contribute to 21.3-35.8% of runoff changes [18].…”
Section: Introductionmentioning
confidence: 99%
“…The pre-assessment need economically evaluates SCP projects comparing with traditional engineered measures (Chang and Su, 2020). The direct comparison of economic costs and benefits can guide decision-making and project selection to maximize the utilizing value of limited resources (Raymond et al, 2017).…”
Section: Improving Scp Assessment Mechanismsmentioning
confidence: 99%